An experimental study on the synergic damage of chemical solutions and stress to coal - Yaoyu Shi; Xiangchun Li; Xiaowei Li; Haonan Song; Xuefei Zhuo; Jianhua Zeng; Zhenzhong Li; Qingdong Qu (Scientific Reports)
Abstract This paper investigates the impact of treatment with chemical solutions of varying pH values on the micro-macroscopic damage in coal samples under load, employing a combination of Small Angle X-ray Scattering (SAXS) experiments and uniaxial compression tests. The experimental results show that soaking coal samples in NaOH, HCl, and distilled water for 7 days leads to reductions in uniaxial compressive strength by 39.19%, 47.26%, and 24.39%, respectively, compared to untreated coal. The elastic modulus exhibited similar reductions, further confirming the weakening effects of chemical solutions. SAXS experiments reveal that exposure to alkaline solutions promotes the expansion and connection of nanopores, while acidic solutions primarily dissolve mineral components, increasing brittleness. Distilled water causes milder effects on pore structure and mechanical properties. To model the synergic effects of chemical solution corrosion and stress, a chemical solution corrosion-stress coupling factor was introduced into the Weibull probability distribution-based constitutive model. The modified model accurately describes the strain–stress behavior and damage evolution under combined chemical and mechanical effects. These findings highlight the risks of chemical solution-induced damage to coal and provide theoretical support for disaster prevention and stability control in coal mining.